Langkah WTO Menyelesaikan Sengketa Pembatasan Impor Daging Sapi dan Hortikultura Antara Indonesia Terhadap Amerika Serikat - Febriza, Salwa (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The World Trade Organization (WTO) serves as a global platform for trade and a policymaking body. All WTO members are bound by agreements and regulations that require them to liberalize trade, including opening their markets to other members. As a member of the WTO, Indonesia is subject to the organization's laws and regulations. This membership allows Indonesia the flexibility to create domestic laws in line with WTO provisions. Trade relations between Indonesia and the United States frequently encounter issues, particularly regarding horticultural import policies and beef import quotas. The United States argues that these policies violate WTO rules and hinder bilateral trade. To safeguard domestic industries from unfair trade practices, remedies such as antidumping measures, compensation, and safeguards are employed under international agreements.